2015
DOI: 10.1016/j.ahj.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the proprotein convertase subtilisin/kexin type 9 inhibitor alirocumab among high cardiovascular risk patients on maximally tolerated statin therapy: The ODYSSEY COMBO I study

Abstract: Alirocumab treatment achieved a significantly greater reduction in LDL-C and allowed a greater proportion of patients to achieve LDL-C goals, versus placebo after 24 weeks in high cardiovascular risk patients with suboptimally controlled hypercholesterolemia at baseline despite receiving maximally tolerated statin with or without other lipid-lowering therapy. The frequency of treatment-emergent adverse events and study medication discontinuations were generally comparable between treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
224
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 301 publications
(242 citation statements)
references
References 12 publications
12
224
1
5
Order By: Relevance
“…This post‐hoc pooled analysis included individuals with a medical history of Type 1 or Type 2 DM and ASCVD who participated in 9 randomized, double‐blind, placebo‐ or ezetimibe‐controlled ODYSSEY Phase 3 trials with subcutaneous alirocumab administered every 2 weeks (Q2W), with trial durations of 24‐104 weeks (LONG TERM [NCT01507831],26 FH I [NCT01623115],23 FH II [NCT01709500],23 HIGH FH [NCT01617655],22 COMBO I [NCT01644175],24 COMBO II [NCT01644188],20 OPTIONS I [NCT01730040],19 OPTIONS II [NCT01730053]21 and ALTERNATIVE [NCT01709513]) 25. Individual trial results have been published previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This post‐hoc pooled analysis included individuals with a medical history of Type 1 or Type 2 DM and ASCVD who participated in 9 randomized, double‐blind, placebo‐ or ezetimibe‐controlled ODYSSEY Phase 3 trials with subcutaneous alirocumab administered every 2 weeks (Q2W), with trial durations of 24‐104 weeks (LONG TERM [NCT01507831],26 FH I [NCT01623115],23 FH II [NCT01709500],23 HIGH FH [NCT01617655],22 COMBO I [NCT01644175],24 COMBO II [NCT01644188],20 OPTIONS I [NCT01730040],19 OPTIONS II [NCT01730053]21 and ALTERNATIVE [NCT01709513]) 25. Individual trial results have been published previously.…”
Section: Methodsmentioning
confidence: 99%
“…Alirocumab is a PCSK9 inhibitor that signficantly reduced LDL‐C and other atherogenic lipid parameters in participants with hypercholesterolaemia in Phase 3 ODYSSEY trials,19, 20, 21, 22, 23, 24, 25, 26 including dedicated trials involving individuals with DM who were receiving insulin therapy27 or with mixed dyslipidaemia,28 with a safety profile comparable to controls. Alirocumab has also been demonstrated to reduce major adverse cardiovascular events vs placebo in patients with recent acute coronary syndrome in the ODYSSEY OUTCOMES trial 29.…”
Section: Introductionmentioning
confidence: 99%
“…Alirocumab, a fully human monoclonal antibody that specifically binds to PCSK9, has been shown to significantly lower LDL‐C levels across a range of dosing regimens, whether as monotherapy12 or on a background of statin±other lipid‐lowering therapies 13, 14, 15, 16. A monthly dosing regimen may be convenient and effective,17, 18 with different doses being appropriate when used as monotherapy compared with background statin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Alirocumab and evolocumab, either alone or in combination with statins and/or other lipid‐lowering therapies, have been shown in their respective phase 3 clinical trial programs (ODYSSEY and PROFICIO [Program to Reduce LDL‐C and Cardiovascular Outcomes Following Inhibition of PCSK9 In Different Populations]) to significantly reduce LDL‐C levels by up to 60% from baseline (depending on dosing regimen; Table) in patients with hypercholesterolemia, including those with familial hypercholesterolemia, moderate to very high cardiovascular risk, and statin intolerance 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62. The inclusion/exclusion criteria and other details of each phase 3 ODYSSEY and PROFICIO trial are shown in Table S2.…”
Section: Pcsk9 Inhibitors and Their Effects In Patients With Diabetesmentioning
confidence: 99%
“…Subanalyses of the diabetes mellitus subpopulations in the alirocumab and evolocumab phase 3 trials (Table) showed significant reductions in LDL‐C that were generally similar between individuals with and without diabetes mellitus 46, 47, 62, 66, 67, 68, 69, 70. Findings were consistent in the prespecified diabetes mellitus subanalysis of FOURIER, which analyzed 11 031 patients with diabetes mellitus versus 16 533 patients without diabetes mellitus; compared with placebo, median LDL‐C levels were reduced by 57% in those with diabetes mellitus and by 60% in those without diabetes mellitus 71.…”
Section: Lipid‐lowering Efficacy Of Pcsk9 Inhibitors In Patients Withmentioning
confidence: 99%